Towards a Greener Future: Factors Impacting Eco-Friendly Shopping Bag Adoption in Retail Sector - Shafia Maulidina Faza; Eka Intan Kumala Putri; Meilanie Buitenzorgy (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2024)
Green consumer behavior relates to product usage that considers environmental impact, such as utilizing eco-friendly shopping bags instead of plastic bags. Internal and external factors, including awareness, expectations, and eco-friendly product marketing influence this behavior. This study analyzes the factors influencing green consumer behavior regarding eco-friendly shopping bag usage. Data were collected from 115 modern retail customers using convinience sampling. The analysis employed descriptive and structural equation modelling techniques. Results indicate that eco-friendly shopping bags as a means to protect future generations from plastic waste’s negative impacts while reducing current environmental plastic waste. The study found that waste sorting and product reuse can overcome the problem of environmental plastic waste. Environmental protection awareness and products marketing significantly influence green consumer behavior. Public awareness of environmentally friendly products can be enhanced through green marketing, which includes disseminating knowledge and information about green consumer behavior. This study suggests that improving public awareness requires promoting environmental protection through eco-friendly product marketing. Additionally, incorporating environmental behavior knowledge into marketing activities can increase green consumer behavior among shopping bag users.